(untitled) (Prostor, 2024)
Antun Baće’s long-awaited book The Architecture of Dubrovnik between the Two World Wars is a truly masterful, meticulous and comprehensive exploration of Dubrovnik’s interwar architectural heritage. The book offers thorough insight into the architecture of the interwar period in Dubrovnik and its immediate surroundings (from Cavtat in the east to Trsteno in the west, including the Elaphite Islands).